Extracellular vesicles derived from osteogenically induced human bone marrow mesenchymal stem cells can modulate lineage commitment - Martins, Margarida Isabel Barros Coelho (2016)
The effective osteogenic commitment of human bone marrow mesenchymal stem cells (hBMSCs) is critical for bone regenerative therapies. Extracellular vesicles (EVs) derived from hBMSCs have a regenerative potential that has been increasingly recognized. Herein, the osteoinductive potential of osteogenically induced hBMSC-EVs was examined. hBMSCs secreted negatively charged nanosized vesicles (â ¼35Â nm) with EV-related surface markers. The yield of EVs over 7Â days was dependent on an osteogenic stimulus (standard chemical cocktail orÂ RUNX2Â cationic-lipid transfection). These EVs were used to sequentially stimulate homotypic uncommitted cells during 7Â days, matching the seeding density of EV parent cells, culture time, and stimuli. Osteogenically committed hBMSC-EVs induced an osteogenic phenotype characterized by marked early induction ofÂ BMP2,Â SP7,Â SPP1,Â BGLAP/IBSP, and alkaline phosphatase. Both EV groups outperformed the currently used osteoinductive strategies. These data show that naturally secreted EVs can guide the osteogenic commitment of hBMSCs in the absence of other chemical or genetic osteoinductors.